HUBUNGAN PENGETAHUAN SISWA TENTANG DUNIA KERJA DENGAN MINAT BEKERJA ATAU MELANJUTKAN STUDI PADA JURUSAN BANGUNAN SMK NEGERI 1 GUGUAK KABUPATEN 50 KOTA - 495-501 , Fauziah Mufthirah (CIVED, 2014)
Abstract   SMK is study of vocational school which was aimed to emphasize readiness students for to enter workfield and expand professional attitude. Yet, not all of SMK students interested to enter the working world, contrary interested for continue study. This research was a know correlation student of the working world with interest work r interested for continue study at direction build SMK Negeri 1 Guguak Kabupaten 50 Kota. This research was a descriptive research corelational, which was aimed to know how wide influence variable (X) towards variable (Y) and type correlation happen. The population of this study was students class X and XII of  whish are 52 students, and The sample was taken by using simple random sampling whish are 35 students. Based on the data analysis, it was assumed that correlative coefficient was (r=0,4402). And then concluded of data analysis is accepted correlation between knowledge about working world with interest work or interest continued study on significantcy 5%.   Key word : Pengetahuan, Dunia Kerja, Minat bekerja, Minat Melanjutkan Studi.